2008
DOI: 10.1063/1.3033749
|View full text |Cite
|
Sign up to set email alerts
|

High intensity, plasma-induced emission from large area ZnO nanorod array cathodes

Abstract: High intensity electron emission cathodes based on a well-aligned ZnO nanorod array were fabricated. An investigation of the properties of the plasma and the electron beams produced by ZnO nanorod array cathodes was presented. Intense current electron beams were obtained from the cathodes. At an electric field of 7–8V∕μm and pulse duration of ∼100ns, the highest emission current density reached 76–91A∕cm2. The production mechanism of the electron beams was the plasma-induced emission. The morphology and struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 20 publications
0
22
1
Order By: Relevance
“…Fig. 4(b) represents CV curves with different scan rates (20,40,60,80 and 100 mV/s) in 3 mM glucose for the kinetic and transport characteristics of GO x /ZnO electrode. It can be found that the oxidation peak potential for H 2 O 2 shifts positively with the increase of scan rates, suggesting a kinetic control over the redox at the active sites of the GO x /ZnO electrode [21].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 4(b) represents CV curves with different scan rates (20,40,60,80 and 100 mV/s) in 3 mM glucose for the kinetic and transport characteristics of GO x /ZnO electrode. It can be found that the oxidation peak potential for H 2 O 2 shifts positively with the increase of scan rates, suggesting a kinetic control over the redox at the active sites of the GO x /ZnO electrode [21].…”
Section: Resultsmentioning
confidence: 99%
“…ZnO nanorods were synthesized by the hydrothermal decomposition method on Si substrates in a large scale. The reaction solution was prepared by mixing proper quantity of 0.05 M Zn(NO 3 ) 2 and methenamine ((CH 2 ) 6 N 4 ) solutions in a Teflon-lined autoclave [20]. The desirable reaction conditions are 95 • C and 7 h. The white colored powder collected from Si wafers, wetted by 0.01 M phosphate buffer solution (PBS) with pH 7.4, were coated onto the surface of a Au electrode, and then dried after being compacted [10].…”
Section: Methodsmentioning
confidence: 99%
“…the application in the plasma-flashover cathodes due to their excellent field emission properties. [3][4][5][6][7][8] Unfortunately, the electron emission properties of ZnO-NAs under the pulse electric field were rarely investigated. Therefore, the studies on the field emission properties of ZnO-NAs are very important under both the pulse electric fields and the DC electric fields.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Field emission properties of 1D nanomaterials has been extensively studied because of its importance in the fundamental and high technology applications. [3][4][5][6] Among them, 1D ZnO nanostructures have been widely investigated as electron emitters, because they have high thermal stability in harsh environments, high aspect ratio and high curvature at the tip.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation